2013
DOI: 10.1111/jace.12240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mg Substitution on Order/disorder Transition, Microstructure, and Microwave Dielectric Characteristics of Ba((Co0.6Zn0.4)1/3Nb2/3)O3 Complex Perovskite Ceramics

Abstract: Effects of Mg substitution on order/disorder transition, microstructure, and microwave dielectric characteristics of Ba((Co0.6Zn0.4)1/3Nb2/3)O3 complex perovskite ceramics have been investigated. The ordered complex perovskite solid solutions are obtained in Ba((Co0.6−x/2Zn0.4−x/2Mgx)1/3Nb2/3)O3 ceramics (x = 0, 0.1, 0.2, and 0.3), and the ordering degree in the as‐sintered dense ceramics increases with increasing Mg‐substitution amount. The significantly improved Qf value is obtained in the present ceramics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 35 publications
1
52
0
Order By: Relevance
“…Figure 6 illustrates the s f value of the Ba(Co 0.6-x Y x Zn 0.38 ) 1/3 Nb 2/3 O 3 (x = 0, 0.01, 0.02, 0.03, 0.04, 0.06) ceramics sintered at 1375°C for 20 h. For a composite ceramic, the s f value primarily depends on its phase composition. In previous studies [4,22], the changes of the s f value presented an increasing tendency as a function of the addition amount for BCZN ceramics, which can be attributed to relatively higher s f value of the secondary phase. The s f values in our work also increased with increasing doping content.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Figure 6 illustrates the s f value of the Ba(Co 0.6-x Y x Zn 0.38 ) 1/3 Nb 2/3 O 3 (x = 0, 0.01, 0.02, 0.03, 0.04, 0.06) ceramics sintered at 1375°C for 20 h. For a composite ceramic, the s f value primarily depends on its phase composition. In previous studies [4,22], the changes of the s f value presented an increasing tendency as a function of the addition amount for BCZN ceramics, which can be attributed to relatively higher s f value of the secondary phase. The s f values in our work also increased with increasing doping content.…”
Section: Resultsmentioning
confidence: 83%
“…5, it is found that there was much relation between the Q 9 f values and the microstructure. Although it is believed that the microwave dielectric loss of the BCZN ceramics is mainly affected by the 1:2 ordered hexagonal structure, the impurity phase, the porosity, and grain size also influence the microwave dielectric loss [4]. The composition exhibiting the optimum microstructure in the field of, e.g., high c/a ratio, pure phase, uniform grain size distribution, few pores composition can usually possess a high Q 9 f value.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations